Upaya Secara Mediasi Sebagai Salah Satu Alternatif Penyelesaian Sengketa Harta Waris - Siti Nur Kholifah; Devi Siti Hamzah Marpaung (Peneliti.net, 2022)
Inheritance is an inheritance owned by a deceased person or commonly called an heir, the inheritance is usually given by the heir to the family or commonly called the heir, with certain provisions divided by the provisions of the inheritance law. This inheritance law can use the provisions of civil law, Islamic law, or customary law. Heirs are quite sensitive, to be discussed openly by the heirs. This can lead to conflicts or settlements that lead to inheritance disputes. Disputes that occur in the community are usually about rights and obligations grouped in civil matters. In addition to the issue of marriage and divorce, inheritance becomes a problem that attracts a lot of public attention. The problem of inheritance that occurs in the community rests on the division of inheritance where only a portion of the heirs control the inheritance; the distribution of an uneven inheritance, the inheritance has been sold by one of the heirs and not approved for the other heir. This issue can be resolved by means of litigation (in court) or non-litigation (out of court).